Pengembangan Desain Kurikulum Pembelajaran RA Bunayya ICBB Sebagai Lembaga Pendidikan Tahfidzul Qur’an - Nisa Fauziah Syahidah; Yelis Nurwahidah (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2025)
In educational units, curriculum is a learning program used by educational institutions to be applied to students, curriculum and education is an educational unit, of course, has a learning design. This study aims to find out about the development of learning curriculum designs as educational institutions for Tahfidzul Qur'an. This research was conducted at RA Bunayya ICBB Yogyakarta. This type of research uses aqualitative method approach in understanding a phenomenon experienced by the subject or research object and describes how the implementation of the Tahfidzul Qur'an curriculum design at RA Bunayya ICBB Yogyakarta. The technique of collecting and collecting data was carried out by interviewing the head of the RA school and one of the teaching staff, as well as through observation and field documentation. Furthermore, from the results of the research, it was found that RA Bunayya ICBB Yogyakarta has implemented the Tahfidzul Qur'an, Tahsin MBB, Hadith, and Arabic curricula which are characteristic of the curriculum design of the At-Turost Al-Islamiy Foundation since the 2005 school year. The target of implementation The design of the Tahfidzul Qur'an curriculum is that all graduates of RA Bin Baz Putri Yogyakarta have the provision of memorizing at least juz 30 and 29 to Surah Al Jinn.